Exercise capacity of male and female national team athletes in canoe slalom - Sitkowski, D.; Starczewski, M.; Pokrywka, A.; Zmijewski, P.; Opaszowski, B.; Klusiewicz, A. (Frontiers in Physiology, 2025)
Introduction: Canoe slalom is a well-established Olympic discipline. However, scientific knowledge regarding the physiological characteristics and training adaptations of its athletes, particularly among females, remains limited. To better characterize their exercise capacity, we retrospectively analyzed exercise test results collected over the past 20 years in our laboratory from both male (n = 110) and female (n = 43) national team members.